Inovasi Pembelajaran E-Learning Dalam Menghadapi New Normal Di SMK Negeri 1 Lawang Wetan - Sulistiawati Sulistiawati; Lukman Hakim; Patricia Hotma Minar Lubis; Rita Sulistyowati; Sugiarti Sugiarti; Lefudin Lefudin (Universitas PGRI Palembang, 2021)
The conditions of the Covid-19 pandemic created conditions that seemed to be